Profit Sharing System "Mabbage" Goats in Supporting The Economy of Women Head Of Households Of Sidereng Rappang District - Fitriawaty; Sulkarnain (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
The profit-sharing system for "Mabbage" goat livestock is unwritten local wisdom and without standard rules in Sidenreng Rappang Regency. "Mabbage" is widely carried out by women heads of households who are difficult to absorb jobs that require high expertise and education. This research is a qualitative descriptive study that aims to describe the form of support for the profit-sharing system of goats in the household economy of women heads of households (widows). The results showed that as many as 16.84% of women head of household in Sidenreng Rappang Regenaverage family dependentspendents of 2-3 people. Raising goats with a profit-sharing system is one of the employment opportunities that absorbs a lot of women headworks head of the household in the age range of 40 years and over with low education. Raising goats is carried out with an extensive pattern that does not require high capital. The profit sharing system is 50:50. The profit sharing system can support the economy of the family of the female head of the household with an additional revenue of Rp. 1,000,000 per month from raising goats with a "Mabbage" system. This activity is a form of empowerment and economic independence of women heads of households.